Electrochemical reduction of gold nanoparticles using scanning electrochemical microscope (SECM) technique - Ali E. Karim (Journal of Madenat Alelem University College, 2024)
A thin film of gold–ions doped microscope slides was synthesized by using the sol-gel method. Firstly, tetraethyl orthosilane ( TEOS) incorporated with AuCl3 was hydrolyzed and then conduced. Microscope slides have been immersed in silica solution for a few minutes to form a thin layer of silica on the slides. Then, the scanning electrochemical microscope (SECM) technique was used for electro reduction of gold ions. Many techniques have been used to characterize the microscope slides before and after the reduction such as scanning electron microscope (SEM), x-ray photoelectron spectroscopy (XPS), optical microscopy, and x-ray diffraction (XRD) calculations.